Methodology and practical implementation of research of changes in forest coverage of Volyn region using remote sensing - Fesyuk, Vasyl; Moroz, Iryna; Fedonyuk, Mykola; Melnyk, Oleksandr; Polyanskyi, Serhii (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Introduction. Forests are an integral component of the environment. However, in recent years, there has been a trend towards deforestation in the Volyn region. The main causes of losses were felling and destruction of forests by pests, diseases and fires. The purpose of the article. The purpose of the study is to develop a methodology for assessing the forest cover of the Volyn region, its verification, assessment of the current state of the forest cover, determination of the trend of change and outline of the main measures to improve the protection and rational use of forest resources. Methods. Research methods: expeditionary (to study the state of forest cover in a specific area of interest), mathematical statistics (for statistical processing of monitoring results), expert evaluation (to establish the reasons for changes in forest cover), remote sensing (to assess the extent of change in forest cover). Used Ecological passports of the Volyn region for 2017-20, materials of own research, data from web services for monitoring the forests, Sentinel-2 satellite images. Results. Data on the area of forests and deforestation in the Volyn region, obtained from various sources, are compared with each other. For example, according to EOS Forest Monitoring data, the area of forests in the Volyn region in 2020 was 1,108 million ha, according to Global Forest Watch – 0,733 million ha, according to the results of determining the area of forests in Google Earth Engine – 0,853 million ha. Forest cover was 55,02%, 36,38% and 42,35%, respectively. According to official information from the Ecological Passport of the region – 34%. Such differences are understandable and are explained by the difference in the method of definition. For the period 2001-21 forest losses amounted to 0,103 million ha. The area of non-forest land for forestry purposes is growing. In 2017, their area amounted to 1692.3 ha, in 2018 - 32459.3 ha, in 2019 - 34136.86 ha, in 2020 - 42436.33 ha. Evidently, in 2018, there were changes in the approach to defining these lands. The area of dead forest plantations is decreasing. If in 2017 it amounted to 2915 ha, then in 2018 it decreased by 43.01%, in 2019 - by another 22.36%, in 2020 - by another 33.22%. Most of the forest plantations died from pests and diseases. The above-mentioned decrease in the area is explained by effective and large-scale sanitary felling in previous years. The area of forests destroyed by fires is insignificant. Forest losses were caused by extreme weather conditions in some years (2017, 2019). Measures for the rational use and protection of forests in the Volyn region are proposed. The scientific novelty consists in an attempt to compare different assessment methods for a definition of the current state of forest cover in the Volyn region and the trend of its change. Practical significance is determined by the possibility of using the obtained results for the development of a set of measures for the rational use and protection of forests in the Volyn region.